Profinite closures of the iterated monodromy groups associated with quadratic polynomials - Samoilovych, I. (Algebra and Discrete Mathematics, 2017)
In this paper we describe the profinite closure of the iterated monodromy groups arising from the arbitrary post-critically finite quadratic polynomial.